Involvement of Epigenomic Factors in Bile Duct Cancer - Rogalska-Taranta, Magdalena; Andersen, Jesper B. (Seminars in Liver Disease, 2022)
Cholangiocarcinoma (CCA) is the second most common type of primary liver cancer. Due to its often-silent manifestation, sporadic nature, and typically late clinical presentation, it remains difficult to diagnose and lacks effective nonsurgical therapeutic options. Extensive research aiming in understanding the mechanisms underlying this disease have provided strong evidence for the significance of epigenetics contributing to its onset, progression, and dissemination. This dysregulation in a myriad of signaling pathways, leading to malignancy, spans altered deoxyribonucleic acid and histone methylation, histone acetylation, and chromatin remodeling, as well as genetic modifications in essential genes controlling these epigenetic processes. An advantage to epigenetic modifications is that they, compared with mutations, are reversible and can partially be controlled by inhibiting the responsible enzymatic machinery. This opens novel possibilities for developing new treatment modalities with benefit for CCA patients.In this article, we have reviewed the current status of epigenome modifications described in CCA, including the role of posttranslational histone modifications and chromatin remodeling, as well as novel advances in treatment options.
Keywords: epigenetics; histone modifications; DNA methylation; IDH; epigenetic therapy; biliary tract cancer; cholangiocarcinoma; CCA